N/P-based Sterically Demanding Ligands: Synthesis, Reactivity and Catalysis - Nolla Saltiel, Roberto (2019)
This thesis details aims at forming low-coordinate metal complexes, stabilised by N-based ligands, with significant focus on carbazole based systems. The sysnthesis of ligands containing these moieties is first targeted, giving a detailed explanation of how differing synthetic pathways that allow modifications to the central carbazole core, in turn allow the formation of stable low-coordinate metal centres. Stabilised metal centres derived from these studies, have been found useful in the dehydrogenation of dimethylamine-borane adducts. While also suitable in the selective anti-Markovnikov hydrophosphination of activated alkenes.